2017
DOI: 10.3382/ps/pew273
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitochondrial function and sperm progressivity in slow- and fast-growing roosters

Abstract: The objectives of the current study were to investigate the activity of the electron transport chain (ETC) complexes, adenosine triphosphate (ATP), and reactive oxygen species (ROS) in the sperm mitochondria of 2 Iranian slow- and fast-growing chickens, namely native and Aryan strains. In this study, semen of 133 roosters was analyzed by computer-assisted sperm analysis (CASA). The roosters were categorized by sperm progressivity, as a low or high sperm motility phenotype. Mitochondrial complex I (NADH ubiquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Mitochondria have a crucial role in the energy metabolism and ATP generation 41 . Sperm motility is found to be directly and positively correlated with mitochondrial respiratory enzyme activity and ATP production in roosters 42 . Our results show plasma conditions can be optimized to enhance chicken sperm motility by increasing the activity of respiratory enzyme and ATP production through upregulation of the mRNA expression of ATP synthase subunits and ATP5A protein level in spermatozoa.…”
Section: Discussionmentioning
confidence: 93%
“…Mitochondria have a crucial role in the energy metabolism and ATP generation 41 . Sperm motility is found to be directly and positively correlated with mitochondrial respiratory enzyme activity and ATP production in roosters 42 . Our results show plasma conditions can be optimized to enhance chicken sperm motility by increasing the activity of respiratory enzyme and ATP production through upregulation of the mRNA expression of ATP synthase subunits and ATP5A protein level in spermatozoa.…”
Section: Discussionmentioning
confidence: 93%
“…Energy metabolism is a key factor supporting sperm functions ( Piomboni et al., 2012 ). Sperm motility has been found to be enhanced by increasing the activity of mitochondrial respiratory enzyme activity and ATP production through upregulation of the mRNA expression of related enzymes in roosters ( Kamali Sangani et al., 2017 , Jiao et al., 2018 ). Analysis of chicken sperm transcriptome by microarray analysis in the present study showed that many DEG significantly enriched in the oxidative phosphorylation pathway, such as NADH dehydrogenase, ubiquinol-cytochrome c reductase, ATP synthase, cytochrome c oxidase, and succinate dehydrogenase, were markedly downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…This has limited the clinical treatments, such as the intra-cytoplasmic sperm injection for poor sperm motility or the immotile sperm [20]. The motility of asthenozoospermatozoa correlated with mitochondrial bioenergy (ATP) generated via oxidative phosphorylation based on the utilisation of the electron transport system [21]. Ultimately, the potential difference of the membrane operates the ATP synthase complex and generates most of the energy used for sperm motility.…”
Section: Discussionmentioning
confidence: 99%